PRE-CONCEPTION READINESS AMONG PROSPECTIVE BRIDES - Syihabul Millah; Devi Arine Kusumawardani, S.Keb., M.Kes.; Septi Nur Rahmawati (Indonesian Midwifery and Health Sciences Journal)
Background: Preconception is the best preparation time for the First 1000 Days of Pregnancy. Prospective brides are a group that must receive attention and monitoring regarding health conditions, including nutritional status, to prepare for pregnancy and the birth of a healthy baby. This research aims to determine the preconception nutritional readiness of prospective brides. Method: This type of research was quantitative with a cross-sectional descriptive design. The population in the study was 30 prospective brides and was obtained using a consecutive sampling technique of 20 prospective brides. The variables studied were the bride and groom's sociodemographic data, including age, highest level of education, work status, and sources of nutrition and health information. Other variables studied were body mass index nutritional status, chronic lack of energy status, anemia status, energy, protein, iron, calcium, folic acid intake, ferro supplementation and folic acid supplementation, and preconception nutritional knowledge. The collected data will be entered and processed using Microsoft Excel and SPSS, then analyzed univariately using a descriptive frequency test. Results: The results of this study show that the sociodemographics of the majority of prospective brides are in the early adult age category (55%), have secondary education (75%), are not working (75%), and receive health and nutritional information from health workers (45%). Adequate energy intake level (75%), insufficient protein (55%), insufficient iron (85%), insufficient calcium (95%), insufficient folic acid (100%), no supplementation (85%), nutritional status of each -respectively normal and obese (35%), not CED (60%), not anemic (80%), lacking knowledge (70%), and lacking preconception nutritional readiness (85%). Conclusion: Most prospective brides cannot meet at least half of the preconception nutritional readiness indicators measured.